1994
DOI: 10.1097/00132586-199402000-00038
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of the Preoperative Investigation of Surgical Patients

Abstract: The pattern of preoperative investigation was audited in 256 patients entering hospital for elective surgery over a 12-week period. During the initial 6 weeks (phase one), no tests are relevant and to minimise unnecessary expenditure. Methods and patientsThe pattern of requests of the five most commonly performed investigations was examined. The investigations were: full blood count (FBC), urea and electrolytes (U&E), blood glucose, chest radiograph (CR) and electrocardiogram (ECG). In phase one of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…The planning phase involved regular meetings of the Royal North Shore Hospital surgical team that consisted of a consultant surgeon and anaesthetist, junior medical officers, PAC nurse screener, and quality manager. An initial audit of 20 randomly selected medical records of patients who had attended the PAC confirmed that >40% of tests ordered were inappropriate, a finding consistent with previous reports 4 .…”
Section: Methodssupporting
confidence: 82%
“…The planning phase involved regular meetings of the Royal North Shore Hospital surgical team that consisted of a consultant surgeon and anaesthetist, junior medical officers, PAC nurse screener, and quality manager. An initial audit of 20 randomly selected medical records of patients who had attended the PAC confirmed that >40% of tests ordered were inappropriate, a finding consistent with previous reports 4 .…”
Section: Methodssupporting
confidence: 82%
“…[13][14][15] Furthermore, most studies of mass screening tests report that 30-95% of unexpected laboratory abnormalities are not documented nor pursued using further investigations. 23,24 There are obvious implications in not pursuing unexpected abnormal results that could potentially increase rather than reduce legal liability. In addition, there is a perception that coagulation tests are inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation was based on an expected incidence of compliant tests of 30% [1, 9] of the patients undergoing surgery; in order to obtain a 95% confidence interval (CI) of 5%, a sample of at least 1,291 subjects was required. However, the sample size was inflated by 15% due to incomplete information in records; therefore, 1,500 subjects were needed in this study.…”
Section: Statisticsmentioning
confidence: 99%
“…The fundamental purposes of preoperative investigations are to obtain information regarding a patient's fitness for anesthesia and surgery and to assess the intraoperative risks [14]. Preoperative investigations were found to be beneficial and cost-effective when they had been correlated with the patients' histories and physical examinations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation